2012
DOI: 10.1186/1471-2407-12-66
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of the KEAP1 gene promoter region in human colorectal cancer

Abstract: BackgroundThe Keap1-Nrf2 pathway has been reported to be impaired in several cancers. However, the status of Keap1-Nrf2 system in human colorectal cancer (CRC) has not been elucidated.MethodsWe used colorectal cancer (CRC) cell lines and surgical specimens to investigate the methylation status of the KEAP1 promoter region as well as expression of Nrf2 and its downstream antioxidative stress genes, NQO-1 and AKR1C1.ResultsDNA sequencing analysis indicated that all mutations detected were synonymous, with no ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
141
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(144 citation statements)
references
References 27 publications
2
141
0
Order By: Relevance
“…[3][4][5] In cancer, NRF2 activation is pro-tumoural in a spectrum of malignancies through mutations in NRF2 or its cytosolic inhibitor KEAP1. [6][7][8][9] However, we have previously shown that in human AML constitutive activation of the NRF2 signalling pathway is not through somatic mutations of NRF2/Keap1 but as a consequence of upstream constitutive activation by NF-κB. 10,11 In addition to contributing to the malignant phenotype of AML, we also found that NRF2 contributes to intrinsic leukaemia cell resistance to standard front-line chemotherapy agents.…”
mentioning
confidence: 95%
“…[3][4][5] In cancer, NRF2 activation is pro-tumoural in a spectrum of malignancies through mutations in NRF2 or its cytosolic inhibitor KEAP1. [6][7][8][9] However, we have previously shown that in human AML constitutive activation of the NRF2 signalling pathway is not through somatic mutations of NRF2/Keap1 but as a consequence of upstream constitutive activation by NF-κB. 10,11 In addition to contributing to the malignant phenotype of AML, we also found that NRF2 contributes to intrinsic leukaemia cell resistance to standard front-line chemotherapy agents.…”
mentioning
confidence: 95%
“…18,26 The presence of two genetic or epigenetic abnormalities was associated with worst progression free survival in patients affected by NSCLC, 18 whereas concomitant methylation of MGMT and KEAP1 genes was able to better predict response to treatment with radiotherapy and temozolomide in malignant gliomas. 26 Hanada et al 27 recently reported aberrant promoter methylation in 53% of colorectal cancer without finding correlation with patients' survival.…”
Section: Patients and Treatmentmentioning
confidence: 99%
“…The promoter region of the KEAP1 gene is hypermethylated in lung (Wang et al 2008a;Muscarella et al 2011), prostate , malignant glioma (Muscarella et al 2011), and colorectal cancers (Hanada et al 2012). The methylation of specific CpG sites within the promoter region of KEAP1 affects KEAP1 expression by inducing local chromatin remodeling and restricting the ability of the transcriptional machinery to bind to the necessary DNA sequences (for review, see Copple 2012).…”
Section: Epigenetic Silencing Of Keap1mentioning
confidence: 99%